Revision of Mesojassus Tillyard, 1916, from the Late Triassic of Queensland (Hemiptera: Cicadomorpha: Membracoidea: Archijassidae) - Lambkin, Kevin J. (Zootaxa, 2020)
New specimens and a re-examination of their holotypes have clarified the status of six nominal species of the extinct membracoid family Archijassidae from the Late Triassic (Norian) fossil insect localities at Mount Crosby, Denmark Hill and Dinmore in south-eastern Queensland. The 57 available tegmina ostensibly attributable to one or other of the six species are remarkably similar in venation and only vary in size and to a lesser extent in shape. The latter character varies subtlety across a continuum and is of no use in species definition. The tegmina, however, fall into two distinct size groups, and in the absence of any other discernible or consistent diagnostic characters, these groups are adopted as separate species, acknowledging, of course, the artificial nature of fossil insect species based on the size only of isolated wings. The following taxonomic changes result: Mesojassus Tillyard, 1916 (= Triassojassus Tillyard, 1919, syn. nov., = Triassocotis Evans, 1956, syn. nov., = Hylicellites Becker-Migdisova, 1962, syn. nov.), Mesojassus ipsviciensis Tillyard, 1916 (= Triassojassus proavitus Tillyard, 1919, syn. nov., = Triassocotis stricta Evans, 1961, syn. nov.), Mesojassus australis (Evans, 1956) comb. nov. (= Triassocotis amplicata Evans, 1961, syn. nov., = Hylicellites reducta (Evans, 1956), syn. nov.). Mesojassus is one of the four genera of the subfamily Archija` ssinae, and differs from the Jurassic Archijassus Handlirsch, 1906, Mesoledra Evans, 1956, and Ardela Ansorge, 1996, in the separation of R and M well before the arculus (at the same level or slightly beyond in the others), the proximal position of dSc, well before the apex of the clavus (at or beyond the apex in the others), and the two-branched RA (simple in the others). The separation of R and M distinctly basal to the arculus, a character of frequent occurrence in extant membracoids, is proposed as a possible apomorphy for this otherwise most plesiomorphic genus of the Membracoidea. Mesojassus, the oldest member of the extant Membracoidea, is one of a growing inventory of genera from the Late Triassic of Queensland which are the oldest representatives of extant groups, adding further evidence of the Triassic as the dawn of much of the modern insect fauna.